Micro- and Nano-Based Transdermal Delivery Systems of Photosensitizing Drugs for the Treatment of Cutaneous Malignancies - Isabella Portugal; Sona Jain; Patrícia Severino; Ronny Priefer (Pharmaceuticals, 2021)
Photodynamic therapy is one of the more unique cancer treatment options available in today’s arsenal against this devastating disease. It has historically been explored in cutaneous lesions due to the possibility of focal/specific effects and minimization of adverse events. Advances in drug delivery have mostly been based on biomaterials, such as liposomal and hybrid lipoidal vesicles, nanoemulsions, microneedling, and laser-assisted photosensitizer delivery systems. This review summarizes the most promising approaches to enhancing the photosensitizers’ transdermal delivery efficacy for the photodynamic treatment for cutaneous pre-cancerous lesions and skin cancers. Additionally, discussions on strategies and advantages in these approaches, as well as summarized challenges, perspectives, and translational potential for future applications, will be discussed.